DISCRETE FRACTIONAL SOLUTION OF A NON-HOMOGENEOUS NON-FUCHSIAN DIFFERENTIAL EQUATIONS - Yilmazer, Resat (Vinca Inst Nuclear Sci, 2019)
In this article, we also present new fractional solutions of the non-homogeneous and homogeneous non-Fuchsian differential equation by using nabla-discrete fractional calculus operator del(alpha) (0 < alpha < 1). So, we acquire new solution of these equation in the discrete fractional form via a newly developed method.
Keywords: discrete fractional calculus; nabla operator; non-Fuchsian equations